ANALISIS BIBLIOMETRIK AUDIT OPERASIONAL MENGGUNAKAN VOSVIEWER DI INDONESIA DENGAN PUBLISH OR PERISH - Audi M, Neysa; Sekar Ayu Pramesti, Amelia; Mitra, Rifa; Oktavia, Zona; Rodiah, Siti (Jurnal Ilmiah Manajemen dan Akuntansi, 2025)
Operational audits serve to assess the effectiveness and efficiency of a company's activities, and provide recommendations for improvement. In an increasingly complex context, these audits have become essential to ensure that companies can meet stakeholder expectations and improve overall performance. This research focuses on a bibliometric analysis of operational auditing in Indonesia, using VOSviewer and Publish or Perish software to explore the characteristics of publications in this field. The main objective of this research is to identify research trends and patterns in the field of operational auditing through a bibliometric approach. The research data was obtained using the Publish or Perish (POP) application. The data collected was obtained from search results containing the keyword “operational auditing” obtained through Google Scholar. This study identified a total of 500 articles from 2000 to 2024. The results showed that the number of operational auditing studies conducted between 2000 and 2024 continued to increase. The analysis showed a close relationship between various keywords that reflect the main focus of the research, such as “technology audit” and “internal audit”.